2022
DOI: 10.1136/emermed-2022-212466
|View full text |Cite
|
Sign up to set email alerts
|

Humans not heroes: Canadian emergency physician experiences during the early COVID-19 pandemic

Abstract: BackgroundThe pandemic has upended much clinical care, irrevocably changing our health systems and thrusting emergency physicians into a time of great uncertainty and change. This study is a follow-up to a survey that examined the early pandemic experience among Canadian emergency physicians and aimed to qualitatively describe the experiences of these physicians during the global pandemic. The study was conducted at a time when Canadian COVID-19 case numbers were low.MethodsThe investigators engaged in an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
(39 reference statements)
0
9
0
2
Order By: Relevance
“…This trend is noted by other studies in high-income countries (( 17 )). The literature indicates that mixed attitudes may stem from inconsistent information from official sources (( 21 24 )), becoming a risk to communication and patient disregard for medical care (( 25 )).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend is noted by other studies in high-income countries (( 17 )). The literature indicates that mixed attitudes may stem from inconsistent information from official sources (( 21 24 )), becoming a risk to communication and patient disregard for medical care (( 25 )).…”
Section: Discussionmentioning
confidence: 99%
“…Although FSMs generally doubted its efficacy, they mainly got vaccinated to obtain the vaccine passport and to protect themselves against serious illness, especially in the case of men. Given the inconsistency of information, also felt among healthcare professionals (( 25 )), FSMs were not always able to count on the news and relied on the recommendations of government agencies, promising a return to normality thanks to vaccination (( 24 , 26 )).…”
Section: Discussionmentioning
confidence: 99%
“…In many nations including Canada, EDs are operating under considerable pressures and limited capacities. Although the COVID-19 pandemic has undoubtedly exacerbated this issue, this is nevertheless not a new problem [ 38 ]. In such stressful and time-sensitive environments, healthcare staff are more likely to face personal and emotional stresses, burnout, and exhaustion [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Still, as cases of infected patients, colleagues, and families increased, physicians’ ability to successfully bounce back from this pandemic trauma eventually declined over time [ 22 ]. In fact, more recent studies examining physicians’ experiences that were conducted during the first and second wave of the pandemic revealed that the positive effects of inter-personal factors (e.g., greater team bonding, respect and thankfulness from both colleagues and the public, and positive institutional dynamics and communication strategies) were short lived and quickly replaced by anxiety and panic in both their personal and professional domains [ 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%